Diseño y construcción de una prótesis ergonómica de pulgar - Cedillo Moncayo, Ulices Rene (2017)
In Ecuador there are people from all ages who require prosthesis, either because they suffered dismemberment or flogging, while there are also people with congenital malformation in their extremities which affect the development on their daily activities, with poor mobility and in more complex cases with a partial or total non-existence of them There are companies that are incharge to the development of different kinds of prosthesis to replace the needs of the people with malformations and flogging, this companies have an approach in which people are only their clients without economic considerations according their social status Innovative humanists with technological-scientific knowledge are in need to create elements that contribute to the community, thus creating animatronic prosthetics that use low cost components and easy to construct in order to help people who are not able to acquire a prosthesis manufactured by companies of internationally know In the next pages, it will be able to find the phases that require the design and construction of an Ergonomic Prosthesis of Thumb focused on a girl with a congenital malformation known as thumb hypoplasia in one of her hands, the design is carried out by using digital devices and CAD software CAM from which 3D digital models are obtained, and then print each one of the components that integrate the prosthesis in 3D, this is electronically controlled by an Arduino Nano plate, in order to achieve the goal of creating a prosthesis built by using components, processes and accessible technology in Ecuador....